154 ANALYSIS OF ELIGIBILITY FOR THROMBOLYSIS IN ISCHAEMIC STROKE PRESENTATIONS IN A UNIVERSITY TEACHING HOSPITAL IN 2021. (25th October 2022) - Healy, C; Noone, I; Meagher, MK; Cassidy, T
Abstract: Background: Since the National Institute of Neurological Disorders and Stroke (NINDS) tissue-type Plasminogen Activator (tPA) trial was published in 1995, thrombolysis has been a mainstay of treatment for ischaemic stroke presenting within the appropriate age-adjusted timeframe, in the absence of contraindications. In the Irish National Audit of Stroke (INAS) National Report 2020, a nationwide thrombolysis rate of 10.6% (Range of 4-22%) was achieved. Aims: (1) This study was designed to compare this centre's rate in 2021; (2) Identifying any missed potentially suitable presentations. Methods: A retrospective chart review of 2021 stroke presentations in this centre was performed using medical admission notes and electronic emergency department records. Excluding haemorrhagic causes, we looked at the presenting National Institutes of Health Stroke Scale (NIHSS), the presenting timeframe and any contraindications of thrombolysis therapy, in order to identify any potentially missed eligible presentations. We also compared the percentage of thrombolysed patients in this centre to the national average. Results: Of the 425 stroke presentations, 74 (17.4%) were excluded as intra-cerebral haemorrhages. Of the remaining 351 presentations, 32 (9.1%) underwent thrombolysis therapy. 225 (64.1%) were not eligible for therapy due to a low or recovering NIHSS (score 0-4). A further 72 (20.5%) with a NIHSS>5, were outside of the window of thrombolysis therapy. Of the remaining presentations, 13 (3.7%) were unsuitable due to anticoagulation use. The final 9 presentations (2.6%) were unsuitable due to other contraindications (previous intracranial haemorrhage, baseline modified Rankin ≥ 4). 18 (5.1%) of non-thrombolysed presentations had no contraindications to thrombolysis therapy aside from late presentation (excluding wake-up events). Conclusion: While this centre's thrombolysis percentage is lower than the national average in 2020, a review of presentations suggests no eligible candidates were missed. Therefore, variations in thrombolysis rates across Irish hospitals may reflect case mix variations rather than decision variations.